The role of semiconductors in the future of optical fibers - Ordu, Mustafa (Frontiers in Physics, 2023)
Semiconductors-core optical fibers have gathered attention for light guidance in the infrared spectrum. Cladded with glasses, fibers can be the ideal medium to transfer the favorable bulk properties of semiconductors into the micro/nano scaled one-dimensional form. The integration of these fibers with optical circuits, lasers and photonic crystals offers a wide variety of applications. In this perspective, the role of semiconductors in the future of optical fibers and their integration with photonic crystal structures are analyzed. The past and present efforts of semiconductor-core fibers are briefly reviewed, and the potential future application areas benefited by semiconductors as fiber materials are discussed.